Rebranding Perpustakaan dalam Perspektif Generasi Z pada Iklan Ponds - Atiqa Nur Latifa Hanum; Aliyah Nur’aini Hanum; Aji Ali Akbar (Institut Agama Islam Negeri Salatiga, 2022)
Advertising is an effective marketing medium in influencing the target market. In the Ponds advertisement, boxing training and libraries as the content became interesting research objects because there were reactions from the audience of the advertisements which indirectly showed how the perspective of libraries among Z generation. This study used a qualitative approach with a critical paradigm to reveal social representations and realities in Ponds advertisements on television and on YouTube channels. Data collection techniques was used documentation and interviews with 10 Z generation informants who have watched the Pond’s White Beauty Facial Foam ads. Data analysis used Stuart Hall reception analysis to analyze the meanings behind the messages conveyed by the Ponds advertisement. Result and discussion showed that the library was described as unfavorite places among the millennial generation on frame of Ponds advertisement. Social reality was obtained that the millennial generation sees the library as the place to read the books and they do not need to go to the library anymore to read. Furthermore, the Ponds advertisement content gave denotative and connotative meanings at the same time. Understanding of libraries needs to be done so as not to trigger misunderstandings among stakeholders, causing negative stigma and stereotypes. The strategy was rebranding the library with an approach to internal and external aspects. Conclusion, the library rebranding effort is a solution to improve the stigma and stereotypes that develop in society. The effectiveness of the rebranding process is determined by the interaction between stakeholders.